From Virtual to Reality: How Metaverse and VR Technologies Influence Travel Decisions - Randi Rian Putra; Ika Devi Perwitasari; Dewi Mahrani Rangkuty; Virdyra Tasril; Sri Handayani; Adinda Silvana Dewi (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study investigates the impact of Virtual Reality (VR) and the Metaverse on travel decisions, specifically focusing on lesser-known tourist destinations. The purpose is to understand how immersive digital experiences can influence potential visitors' perceptions and travel intentions. A mixed-methods approach, combining qualitative interviews with tourism stakeholders and quantitative surveys with 500 participants, was used to collect data. The results show that VR and Metaverse experiences significantly enhance user engagement, emotional attachment, and the likelihood of visiting the destination in person. The study's findings offer practical insights for tourism marketing strategies, suggesting that VR and Metaverse platforms can complement traditional marketing approaches. Theoretical implications include contributing to the understanding of digital transformation in tourism, particularly in how immersive technologies shape travel behavior. This research contributes to both theory and practice by highlighting the potential for VR and Metaverse technologies to increase the appeal of lesser-known destinations like Lake Toba.